Socio‐economic security of the Voronezh region - N. V. Yakovenko; R. V. Ten (Юг России: экология, развитие, 2022)
Aim. The purpose of the study was to assess the socio‐economic security of the municipalities of the Voronezh Region on the basis of a developed methodology.Material and Methods. The information base of the study was made up of official data of the Federal State Statistics Service. To measure the socio‐economic security of the region, the following methods were used: comparison of macroeconomic indicators with threshold values; assessment of the dynamics of changes in the rates of socio‐economic growth of the region; cartographic tools.Results. The results of the calculations of the integral index of socio‐economic security made it possible to identify 5 groups of municipalities that have a certain degree of socio‐economic security: high; medium, below average, low and crisis. It is the crisis situation of a number of municipalities that indicates the need to develop certain anti‐crisis recommendations that contribute to the effective use of existing potential and directly develop the internal resources of municipalities.Conclusion. The assessment conducted of the indicators of socio‐economic security of the municipalities of the region will make it possible to determine the "strengths and weaknesses" of the regional socio‐economic system of the Voronezh region and to develop strategic directions for the implementation of a single strategic goal: improving the level and quality of life of the population. The authors’ approach can be used as a basis for further monitoring of socio‐economic security, which would involve expanding the range of analyzed indicators, as well as conducting regular calculations and comparisons.